Endovascular Treatment of Pelvic Congestion Syndrome: Visual Analog Scale Follow-Up - Senechal, Quentin; Echegut, Perrine; Bravetti, Marine; Florin, Marie; Jarboui, Lamia; Bouaboua, Mehdi; Teriitehau, Christophe; Feignoux, Jacques; Legou, Francois; Pessis, Eric (Frontiers in Cardiovascular Medicine, 2021)
Purpose: To evaluate medium-term clinical outcomes of transcatheter embolization and stenting in women with several pelvic venous disorders responsible for chronic pelvic pain and varicose veins of the lower limbs. Materials and Methods: The study population included 327 consecutively recruited patients referred to the interventional radiology unit from January 2014 to December 2019 due to chronic pelvic congestion (91; 27.83%), lower limb varices (15; 4.59%), or a combination of both the symptoms (221; 67.58%). Preprocedural pelvic, transvaginal Doppler ultrasound (US), and MRI were conducted in all the patients and revealed anatomical varicosities and incompetent pelvic veins in 312 patients. In all the patients, selective catheterization demonstrated uterine venous engorgement, ovarian plexus congestion, or pelvic vein filling. Retrograde flow was detected on catheter venography in the left ovarian vein (250; 78%), the right ovarian vein (85; 26%), the left internal iliac vein (222; 68%), and the right internal iliac vein (185; 57%). Patients were followed-up at 1, 6, and 12 months, and years thereafter systematically by the referring angiologist and the interventional radiologist of center. They were contacted by telephone in November and December 2020 to assess pain perception and quality of life by using the visual analog scales from 0 to 10 with assessments made at the baseline and last follow-up. Of the 327 patients (mean age, 42 ± 12 years), 312 patients were suffering from pelvic congestion syndrome and 236 patients was suffering from lower limb varices. All underwent embolization by using ethylene vinyl alcohol copolymer (Onyx®). Eighty-five right ovarian veins, 249 left ovarian veins, 510 tributaries of the right internal iliac vein, and 624 tributaries of the left internal iliac vein were embolized. A cohort of patients also underwent nutcracker syndrome angioplasty (6.7%) and May–Thurner syndrome angioplasty (14%) with a stent placement. Results: The initial technical success rate was 80.9% for embolization of pathological veins and 100% for stenting of stenoses. Overall, 307 patients attended 12-month follow-up visits and 288 (82%) patients completed the telephone survey at mean 39 (±18)-month postintervention. Main pelvic pain significantly improved from 6.9 (±2.4) pre- to 2.0 (±2.4) postembolization (p < 0.001), as did specific symptoms in each category. Improvement or disappearance of pain was achieved in 266/288 (92.36%) patients with improved quality of life in 276/288 (95.8%) patients. There were 16 minor and 4 major adverse events reported on the follow-up. Conclusion: Pelvic vein embolization (Onyx®) is an effective and safe procedure with high clinical success and quality of life improvement rates.